EFFICACY OF VIMPAT (LACOSAMIDE) TN THE TREATMENT OF DRUG-RESISTANT CRYPTOGENIC FOCAL EPILEPSY WITH FOCAL AUTOMOTOR AND SECONDARILY GENERALIZED SEIZURES (A CLINICAL CASE) - M. B. Mironov; K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии, 2015)
Despite the considerable advances of epileptology drug-resistant epilepsies consist about 30% among all forms of epilepsy. A case of successful using of a new antiepileptic drug lacosamide (vimpat) in the treatment of 31 years old patient with the resistant form of cryptogenic focal epilepsy with focal automotor and secondarily generalized seizures is presented. Authors represent the review of the literature devoted to efficacy and tolerability of lacosamide in the treatment of drug-resistant epilepsy.